Pemberantasan Kejahatan Perbankan Antar Negara Yang Belum Melakukan Perjanjian Ekstradisi (Studi Kasus Maria Pauline Lumowa) - Lesnussa, Vanesia; Wattimena, Josina Augustina Yvonne; Tahamata, Lucia Charlota Octovina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: There are many phenomena of corruption where the perpetrators flee abroad, making it difficult to eradicate corruption. Based on data from Indonesia Corruption Watch (ICW) there are more than 30 fugitives for corruption who have fled abroad and resulted in state losses of around IDR 53 trillion. Indonesia as a country prone to corruption requires international cooperation in dealing with cross-border crimes such as economic crimes in the banking sector.Purposes of the Research: This paper aims to analyze and find out the extradition mechanism in banking crimes for countries that have not entered into an extradition treaty. As well as to analyze and find out legal remedies to return criminal assets to the state according to law return of criminal assets to the state according to international law.Methods of the Research: The research method in this writing is a qualitative analysis method, the type of research is normative research, the research approach used is the statutory approach, the case approach, and the concept approach. The procedure for collecting legal materials uses primary legal materials, secondary legal materials and tertiary legal materials.Results of the Research: The results of the study show that the mechanism or procedure for extradition requests between countries that have not entered into an extradition agreement is the same as the mechanism or procedure for extradition requests with extradition agreements, while legal remedies for returning assets resulting from criminal acts to countries according to international law there are two ways of resolution, namely, first through mutual legal assistance and secondly based on good relations between the two countries this has been regulated in Article 51 and Article 58 of UNCAC 2003